2014
DOI: 10.2514/1.j052242
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Analysis of PrandtlPlane Joined Wings: Effects of Anisotropy

Abstract: Structural geometrical nonlinearities strongly affect the response of Joined Wings: it has been shown that buckling evaluations using linear methods are unreliable and only a fully nonlinear stability analysis can safely identify the unstable state. This work focuses on the understanding of the main physical mechanisms driving the wing system's response and the snap-buckling instability. Several counterintuitive effects typical of unconventional non-planar wing systems are discussed and explained. In particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 29 publications
2
38
1
Order By: Relevance
“…3) is a PrandtlPlane-like configuration (see Demasi et al, 2013b;Cavallaro et al, 2012Cavallaro et al, , 2014a) featuring a swept-back lower wing and a swept-forward upper wing. It is named PrP40.…”
Section: Description Of the Analyzed Joined Wing Configurationsmentioning
confidence: 99%
“…3) is a PrandtlPlane-like configuration (see Demasi et al, 2013b;Cavallaro et al, 2012Cavallaro et al, , 2014a) featuring a swept-back lower wing and a swept-forward upper wing. It is named PrP40.…”
Section: Description Of the Analyzed Joined Wing Configurationsmentioning
confidence: 99%
“…Lastly, we propose that the application of an inverted joined wing configuration could also help in solving the problem of global buckling of the joined wing airplanes reported by several researchers [18][19][20]. The direction of critical load (lift + drag in point A of the load envelope) points upwards and forwards.…”
Section: Introductionmentioning
confidence: 87%
“…Snap-Buckling Recent studies [94,95] have suggested that the unique nonlinear structural response of the box-wing aircraft configuration requires a specialized treatment for buckling. Indeed, these studies demonstrate the unreliability of linear buckling theory, which often leads to an overstimation of the critical load point.…”
Section: Multi-point Optimizationmentioning
confidence: 99%